THE EFFECT OF SECANG WOOD EXTRACT ON HISTOPATHOLOGICAL DESCRIPTION OF THE KIDNEY OF MALE MOUSE POST EXPOSURE TO CONVENTIONAL CIGARETTE SMOKE - Sarungallo, Yoga Pratama Mambela; Berata, I Ketut; Merdana, I Made (Buletin Veteriner Udayana; Vol. 15 No. 3 June 2023DO - 10.24843/bulvet.2023.v15.i03.p13, 2022)
Indonesia is one of the developing countries that has a high number of smokers and cigarette production. Cigarettes are not only harmful to the smoker, but also harmful to those around them who inhale the smoke. Organ damage caused by free radicals from cigarette smoke can be repaired with antioxidants. One of the plants in Indonesia that contains antioxidants is sappan wood (Caesalpinia sappan linn). This study aims to determine the effect of sappan wood extract on the histopathological picture of male mice (Mus musculus) exposed to conventional cigarette smoke for 30 days. This study used kidney samples of male mice, adults aged 35-45 days and body weight between 30-35g totaling 24 individuals. Mice were divided into 4 groups, each group consisted of 6 mice. The experimental animals were isolated on the 30th day, then the kidney histopathological examination of mice was performed. The results of histopathological observations of male mice's kidneys showed varying degrees of severity. The results of Kruskal Wallis' analysis of histopathological examination data were scored, showing a significant difference (p<0.05) for both necrotizing and inflammatory lesions. From the results of the study, it can be concluded that administration of secang wood extract at a dose of 30 mg/30 g BW of mice/day and 60 mg/30 g BW of mice/day can improve kidney lesions of male mice due to exposure to cigarette smoke, based on the reduction of necrotizing and inflammatory lesions. Further research is needed with increasing doses and longer time to determine the effective dose of secang wood extract in reducing kidney damage due to exposure to cigarette smoke in mice.